2020
DOI: 10.2147/ndt.s230403
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of Cognitive Symptoms on Health-Related Quality of Life and Work Productivity in Chinese Patients with Major Depressive Disorder: Results from the PROACT Study</p>

Abstract: Purpose: This post hoc analysis was undertaken to further explore the association of cognitive symptoms with health-related quality of life (HRQoL) and work productivity at the time of treatment initiation in Chinese patients with major depressive disorder (MDD) in the Prospective Research Observation to Assess Cognition in Treated patients with MDD (PROACT) study. Patients and Methods: This was an epidemiological, non-interventional, prospective cohort study in adult outpatients with moderate-to-severe MDD in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…It seems reasonable to assume that the observed improvement in functioning seen in patients with MDD during treatment with vortioxetine may at least in part be due to the beneficial effect of treatment on cognitive symptoms. Indeed, previous studies have shown an independent association between severity of cognitive symptoms and impairment in functioning and workplace performance in patients with MDD ( 14 18 ). A significant association between the severity of patient-reported cognitive symptoms (assessed using the PDQ-D-5) and health-related quality of life (assessed using the EQ-5D) has also been previously reported ( 59 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It seems reasonable to assume that the observed improvement in functioning seen in patients with MDD during treatment with vortioxetine may at least in part be due to the beneficial effect of treatment on cognitive symptoms. Indeed, previous studies have shown an independent association between severity of cognitive symptoms and impairment in functioning and workplace performance in patients with MDD ( 14 18 ). A significant association between the severity of patient-reported cognitive symptoms (assessed using the PDQ-D-5) and health-related quality of life (assessed using the EQ-5D) has also been previously reported ( 59 ).…”
Section: Discussionmentioning
confidence: 93%
“…Cognitive symptoms are common in patients with MDD, with deficits observed across multiple domains including executive function, memory, and attention (10)(11)(12)(13). Numerous studies have shown a significant association between cognitive symptoms and functioning in MDD, which appears to be independent of the severity of mood symptoms (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive and functional symptoms in MDD are also inherently linked, so any improvement in cognitive and functional impairment associated with vortioxetine may be expected to improve quality of life and productivity among Chinese patients with MDD. 19 , 20 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…The study planned to enroll 1000 participants, assuming that information would not be available for 40% of participants at week 8 and 38% at week 24. 20 These participant numbers were expected to result in a precision of 8% and 7% for SDS assessments at weeks 8 and 24, respectively. This also allowed for the rule of 3 to be applied for safety assessments; namely, that if an AE is not observed, there is a 95% probability of the AE occurring in <0.3% of patients.…”
Section: Methodsmentioning
confidence: 99%
“…Its global prevalence is estimated to be 2.4%, such a high rate that the disease should be taken seriously by people [ 4 ]. Major depression is defined by having these symptoms every day for at least 2 weeks: a depressed mood during most times of the day, and loss of interest in normal activities and relationships [ 5 ]. The global prevalence of major depression is approximately 11% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%